Application of Auto-Switched Capacitor Bank to Mitigate Voltage Collapse Problem in Distribution System; A Case Study of Osogbo South –Western, Nigeria. (International Journal of Scientific Research and Management (IJSRM), 2018)
Exponential demand for electrical power supply caused by increased use of electricity at both domestic and industrial level pose threat to power system stability. The need to enhance power system with adequate compensation via reactive power supply becomes a necessity. This paper therefore presents application of auto-switched capacitor bank to mitigate voltage collapse problem; a case study of Osogbo South-Western, Nigeria. The proposed approach carefully design the correct size of capacitor required to supply the reactive power needed for compensation. The obtained values were used to model the power system. The modeled system was subjected to disturbances with a view to investigate its performance. The results obtained showed that the designed capacitor bank was able to stabilize the voltage on the line despite the heavy loads on the power system.